EFEKTIVITAS KEGIATAN MA'HAD MTS NUR RAHMA KOTA BENGKULU DALAM MENINGKATKAN AKHLAK SISWA - Juni Astuti, Dina Putri; Mardianti, Yolanda; Tenri Bela, Shelda; Raihan, Muhammad; Dwi Putri, Puspa (FAKULTAS TARBIYAH UNIVERSITAS QOMARUDDIN GRESIK - JAWA TIMUR, 2025)
This research aims to analyze the effectiveness of Ma'had activities at MTs Nur Rahma, Bengkulu City in improving student morals. The approach used is a qualitative method with data collection techniques through observation, interviews and documentation. The research results show that programs at Ma'had, such as tahfidzul Qur'an, Islamic studies, habituation to worship, and character development, have a significant role in shaping students' better morals. Factors supporting the effectiveness of this activity include the role of the teacher, a conducive environment, and support from parents. However, there are also obstacles such as lack of student participation in several activities and limited facilities. This research recommends strengthening more innovative learning strategies and improving facilities and infrastructure to increase the effectiveness of Ma'had activities in shaping student character